Determination of the prevalence and predictors of ventricular thrombus with assessment of the risk of systemic embolization to the CNS in patients after acute myocardial infarction using magnetic resonance imaging, echocardiography and cardiac markers - a prospective, unicentric, observational study - Hudec, Stepan; Hutyra, Martin; Precek, Jan; Latal, Jan; Nykl, Radomir; Spacek, Miloslav; Sluka, Martin; Sanak, Daniel; Tudos, Zbynek; Pastucha, Dalibor; Taborsky, Milos (Biomedical papers, 2025)
Background. Left ventricular thrombus (LVT) formation is one of the well-known and serious complications of acute myocardial infarction (AMI) due to the risk of systemic arterial embolization (SE). To diagnose LVT, echocardiography (TTE) is used. Late gadolinium-enhanced cardiovascular magnetic resonance (DE-CMR) is the gold standard for diagnosing LVT. Objectives. The aim of this observational study was to determine the role of transthoracic echocardiography and cardiac markers in predicting the occurrence of LVT compared with a reference cardiac imaging (DE-CMR) and to determine the risk of systemic embolization to the CNS using brain MRA. Methods. Seventy patients after MI managed by percutaneous coronary intervention (localization: 92.9% anterior wall, 7% other; median age 58.7 years) were initially examined by transthoracic echocardiography (TTE, n=69) with a focus on LVT detection. Patients were then referred for DE-CMR (n=55). Laboratory determination of cardiac markers (Troponin T and NTproBNP) was carried out in all. Brain MRA was performed 1 year apart (n=51). Results. The prevalence of LVT detected by echocardiography: (n=11/69, i.e. 15.9%); by DE-CMR: (n=9/55, i.e. 16.7%). Statistically significant parameters to predict the occurrence of LVT after AMI (cut off value): (a) detected by echocardiography: anamnestic data - delay (≥ 5 hours), echocardiographic parameters - left atrial volume index (LAVI≥ 32 mL/m2), LV EF Simpson biplane and estimated (≤ 42%), tissue Doppler determination of septal A wave velocity (≤ 7.5cm/s); (b) detected by DE-CMR: anamnestic data - delay (≥ 13 hours), DE-CMR parameters - left ventricular end-diastolic diameter (≥ 54mm). The value of cardiac markers (Troponin T and NTproBNP in ng/L) in LVT detected by echocardiography did not reach statistical significance. In LVT detected by DE-CMR, NTproBNP was statistically significantly increased at 1 month after AMI onset (no optimal cut-off value could be determined). There was no statistically significant association between the LVT detection (both modalities) and the occurrence of clinically manifest and silent cardioembolic events. Conclusion. Our study confirmed a relatively high prevalence of LVT in the high-risk group of patients with anterior wall STEMI. Due to the low prevalence of thromboembolic complications, no significant association between the LVT detection and the occurrence of a cardioembolic event was demonstrated.
Keywords: ventricular thrombus; ST-elevation myocardial infarction; predictors of ventricular thrombus; stroke